2019
DOI: 10.3390/ijms20122919
|View full text |Cite
|
Sign up to set email alerts
|

Chromogranin-A Expression as a Novel Biomarker for Early Diagnosis of Colon Cancer Patients

Abstract: Colon cancer is one of the major causes of cancer death worldwide. The five-year survival rate for the early-stage patients is more than 90%, and only around 10% for the later stages. Moreover, half of the colon cancer patients have been clinically diagnosed at the later stages. It is; therefore, of importance to enhance the ability for the early diagnosis of colon cancer. Taking advantages from our previous studies, there are several potential biomarkers which have been associated with the early diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 45 publications
(66 reference statements)
0
41
0
Order By: Relevance
“…Here we show that the permeability of the gut barrier is finetuned by a major gut hormone, Chromogranin A (CgA). CgA is an acidic secretory proprotein [13][14][15] that is --abundantly expressed in enteroendocrine cells (EEC) of the gut and serves as a common marker for the EEC of the gut 16,17 . As a proprotein, CgA gives rise to several peptides of biological importance: catestatin (CST: hCgA352-372) 18 , pancreastatin (PST: hCgA250-301) 19 , WE14 20 , vasostatin 21 , and serpinin 22 ; we show that CST is abundantly processed in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…Here we show that the permeability of the gut barrier is finetuned by a major gut hormone, Chromogranin A (CgA). CgA is an acidic secretory proprotein [13][14][15] that is --abundantly expressed in enteroendocrine cells (EEC) of the gut and serves as a common marker for the EEC of the gut 16,17 . As a proprotein, CgA gives rise to several peptides of biological importance: catestatin (CST: hCgA352-372) 18 , pancreastatin (PST: hCgA250-301) 19 , WE14 20 , vasostatin 21 , and serpinin 22 ; we show that CST is abundantly processed in the gut.…”
Section: Introductionmentioning
confidence: 99%
“…Even though no signi cant association between CHGA expression and overall survival time of GC patients was observed (Fig. 5G), CHGA has been reported to be an early diagnosis biomarker for GC [26,29] . Here, our preliminary results suggest that XAGE-1b could be regarded as an oncogene for GC progression through the potential downstream molecules, CLDN6 and CHGA.…”
Section: Discussionmentioning
confidence: 96%
“…Our results and previous studies [24,25] suggested that CLDN6 was upregulated in GC tissues and correlated with a decreased survival time in GC patients. Human chromogranin-A (CHGA), a member of the chromogranin/secretogranin family, has been reported to be associated with several tumors [26][27][28] . Even though no signi cant association between CHGA expression and overall survival time of GC patients was observed (Fig.…”
Section: Discussionmentioning
confidence: 99%
“… 4 However, patients with early diagnosed CC are not common in clinic, mainly because the patient’s condition cannot be accurately detected by routine physical examination. 5 Serum tumor markers CA199 and CEA have certain value in the diagnosis of CC, but their specificity is low. 6 Therefore, it is urgent to develop rapid and highly sensitive CC screening markers to improve this situation.…”
Section: Introductionmentioning
confidence: 99%